Meibography guided intraductal meibomian gland probing using real-time infrared video feed - Maskin, Steven L (Br J Ophthalmol, 2020)
PURPOSE: To evaluate use of infrared meibography video to visualise meibomian gland probing and correlate probe findings of intraductal space with meibography images. METHODS: Videos were reviewed and probe findings recorded of 996 probed gland orifices from 38 lower lids. RESULTS: 996/997 (99.9%) of gland orifices were successfully probed with 91.8% revealing probe location. There were no false passages. 14% (140/997) of all gland orifices showed whole gland atrophy (WGA) with 99.3% (139/140) probed to 1 mm. Cumulative probe findings for all WGA (not differ significantly from non-WGA) showed 106 (76%), 21 (15%) and 12 (9%) glands with fixed, non-fixed and no resistance (NR), respectively. Lids without WGA showed increased NR/total glands probed while lids with WGAs (≥5) showed increased NR/WGA compared with lids with only 1–4 WGAs (p=0.011, p=0.005, respectively, Mann-Whitney U test) suggesting bimodal NR profile. Visualisation of microtube placement was successfully obtained for therapeutic injections and retrieval of meibum specimens. CONCLUSION: Video confirmed intraductal location and safety of devices. For 73% of non-WGA and 76% of WGAs as well as proximal ducts of glands with proximal atrophy, probing released fixed resistance restoring ductal integrity. A bimodal profile of NR suggests it is found with less diseased gland ducts as well as more advanced atrophic gland disease. Gland and ducts appeared flexible but not distendable while periglandular tissue appeared spongy. Visualisation of devices enables whole or localised gland therapy and meibum specimen retrieval, elegantly raising future research, therapeutic and regenerative opportunities.